(untitled) (Culturas Científicas, 2023)
In correspondence with the modal interpretations of quantum mechanics, Lombardi and Castagnino (2008) and da Costa, Lombardi and Lastiri (2013) have proposed an ontology of bundles of possible intrinsic properties for quantum mechanics, focused mainly on the issues of quantum contextuality and indistinguishability. Corresponding to the interpretation known as "relational quantum mechanics" (Rovelli, 1996), two ontologies based on relations have been proposed. Laura Candiotto (2017) advocates for a radical metaphysics of relations, considered by the author as an instance of the so-called "ontic structural realism". Alternatively, Andrea Oldofredi (2021) proposes an ontology of bundles of relations, considered by the author as an instance of the so-called "moderate structural realism". Since the 1980s, the topic of quantum entanglement has led several authors (Teller, Healey, Howard, Esfeld) to defend that quantum mechanics involves a form of holism. It has been argued that the holism of quantum mechanics supports the metaphysical thesis known as "priority monism" (Schaffer, 2010a). In this article, an ontology of quantum mechanics is proposed in which the properties of quantum systems have both a modal and a relational character. As a result, a holistic ontology of quantum mechanics is obtained, which is an instance of priority monism and moderate structural realism.